Lockhart Clarke's contribution to the description of amyotrophic lateral sclerosis. - Turner, M; Swash, M; Ebers, G (2010)
The definition of the clinicopathological entity of amyotrophic lateral sclerosis evolved over half a century. Although the definitive term amyotrophic lateral sclerosis that acknowledged both upper and lower motor neuron involvement was attributed to Jean-Martin Charcot in 1874, his initial case was published nearly a decade earlier; and it is accepted that, from at least the 1830s, several others (including Charles Bell, François-Amilcar Aran and Jean Cruveilhier) had already recognized a progressive lower motor neuron-only syndrome within a broader, clinically-defined group of disorders, termed progressive muscular atrophy. Although William Gowers first grouped the three phenotypes of amyotrophic lateral sclerosis, progressive muscular atrophy and progressive bulbar palsy together as part of the same syndrome, the term motor neuron disease, as an over-arching label, was not suggested until nearly a century later by W. Russell Brain. Augustus Jacob Lockhart Clarke (1817-80) is best known for his descriptions of spinal cord anatomy. However, in two detailed case reports from the 1860s, he carried out rigorous post-mortem neuropathological studies of what appear to be classical cases of amyotrophic lateral sclerosis. Furthermore, he recognized the additional involvement of the corticospinal tracts that distinguished this from progressive muscular atrophy. Several aspects of the exquisite clinical histories documented as part of both studies, one by Charles Bland Radcliffe, resonate with contemporary debates concerning the evolution of disease in amyotrophic lateral sclerosis. These 'past masters' still have much to teach us.